Parametric investigation and classification of quadratic equation (2013)
This study investigated the papramters space of simple and familiar quadratic equation often encounter in science based disciplines and in particular engineering.The aim is strange images creation to excite and launch novices to quest for general understanding of fractal taking parallel clue from Julia and Mandelbrot sets creation using the iterative mechanisms of complex quadratic mapping